1985
DOI: 10.1042/bj2250557
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the behaviour in vivo of two molecular forms of antithrombin III

Abstract: The distribution and rates of catabolism were determined for rabbit antithrombin III (AT) isoforms differing in affinity for heparin-agarose. After isolation from rabbit plasma by heparin-affinity chromatography, the very-high-affinity form, ATvh, was labelled with 131I, and its high-affinity congener, ATh, with 125I. The two forms were separated from free iodine by heparin-affinity chromatography, and then injected simultaneously into young recipient rabbits. The disappearance-of-plasma-AT-radioactivity data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 18 publications
4
5
0
2
Order By: Relevance
“…The fact that thrombin inhibition was incomplete in 30 s also facilitated comparison of relative catalytic effects of low doses of glycosaminoglycans. Two complexes of human thrombin with both rabbit antithrombin III and heparin cofactor II were detected when the thrombin was added to rabbit plasma containing a variety of glycosaminoglycans; a finding consistent with previous observations (18,19).As shown in Figures 6 and 7, these complexes of thrombin with heparin cofactor II were sufficiently separated from those of thrombin with antithrombin III after electrophoresis to permit their quantitation.…”
Section: Discussionsupporting
confidence: 89%
“…The fact that thrombin inhibition was incomplete in 30 s also facilitated comparison of relative catalytic effects of low doses of glycosaminoglycans. Two complexes of human thrombin with both rabbit antithrombin III and heparin cofactor II were detected when the thrombin was added to rabbit plasma containing a variety of glycosaminoglycans; a finding consistent with previous observations (18,19).As shown in Figures 6 and 7, these complexes of thrombin with heparin cofactor II were sufficiently separated from those of thrombin with antithrombin III after electrophoresis to permit their quantitation.…”
Section: Discussionsupporting
confidence: 89%
“…Carlson et al 27 reported and we 29 have confirmed that the fractional catabolic rate of rabbit ATIII-£ in the vascular compartment and its fractional distribution in the extravascular compartment in the rabbit are substantially greater than corresponding values for ATIII-a. We infer from the comparative behavior of the isoforms in vivo and from the effects of thrombin in vitro (Figures 2 and 6) that the subendothelium-bound /3 isoform reacts more readily than a with thrombin on or within the vascular wall.…”
supporting
confidence: 66%
“…In that study, the authors deduced that a substantial proportion of antithrombin was contained in association with the vascular wall, a conclusion that others have since verified using other approaches (11,20,31). We have also studied the in vivo behaviors of the ␣and ␤-glycoforms of rabbit antithrombin (30) and found good agreement with the results previously reported for the rabbit antithrombin glycoforms (4). In addition, we have used the same three-compartment method to compare the in vivo behaviors of antithrombin and prothrombin in the rabbit circulation (13).…”
Section: Discussionsupporting
confidence: 87%